ANALYSIS OF ADVERSE DRUG REACTIONS SPONTANEOUSLY REPORTED TO ADVERSE DRUG MONITORING CENTRE OF A TERTIARY CARE HOSPITAL–PROSPECTIVE STUDY - Kulkarni, Gajanan P.; Patil, Lokesh V. (International Journal of Current Pharmaceutical Research, 2018)
Objective: To assess ADRs with reference to causative drugs, organ systems involved and seriousness of reactions. Methods: A prospective study conducted over a period of 1 y. The spontaneous adverse drug reactions reported between July 2016 and July 2017 at AMC centre BRIMS, Bidar were analyzed using Naranjo's scale. Causality assessment of suspected drugs involved, system affected, and seriousness of reactions was assessed. Results: GIT system was most commonly involved, followed by generalized features, skin and appendages, CNS i. e, extrapyramidal system and dizziness, hearing and vestibular systems. Conclusion: Majority of the ADRs reported were mild to moderate severity and 20% can be categorized as severe reactions, which needed to treat under hospitalization